If by sea : the forging of the American Navy-- from the American Revolution to the War of 1812 - Daughan, George C. (New York : Basic Books, 2008)
Chronicles the history of the United States Navy from its creation during the American Revolution to the War of 1812, including the political and economic issues surrounding its creation and development.
Whaleboats and Men-of-War -- Launching the Continental Navy -- Battles in Charleston, New York, and New Jersey -- Saratoga and Philadelphia -- The French Alliance -- Denouement -- A New Republic -- Washington and the Federal Navy -- John Adams builds a navy -- The quasi-war with France -- The navy under Jefferson -- Peaceful coercion -- War clouds -- The navy surprises -- The navy established.
Includes bibliographical references (pages 505-521) and index.
Keywords: United States. -- Navy -- History -- Revolution, 1775-1783.; United States. -- Navy -- History -- 19th century; United States -- History, Naval -- 18th century; United States -- History, Naval -- 19th century; United States -- Politics and government -- 1783-1865.